Aid, education and adventure : an exploration of the impact of development scholarship schemes on women's lives : a thesis presented in fulfilment of the requirements for the degree of Doctorate of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Wild, Kirsten Leila (Massey University, 2007)
This thesis examines the outcomes associated with women’s participation in development scholarship schemes. These schemes, which provide citizens from Third World countries with opportunities to undertake tertiary training abroad, have featured prominently within the development assistance programmes of many Western nations. However, the longer-term impact of this type of educational experience on the lives and communities of individuals who take up this form of aid remains under-studied. This is particularly the case for female development scholars, who have been both historically excluded from opportunities to take part in these schemes, as well as marginalised within academic evaluations of their outcomes. This research provides an in-depth qualitative exploration of the experiences of twenty women who have completed a tertiary qualification through a development scholarship scheme. The participant sample is diverse, and includes a group of New Zealand-based female doctoral students who have participated in several of these programmes, as well as two groups of women from Thailand who have returned home after taking part in a scholarship scheme funded by the New Zealand Agency for International Development. This research identifies a number of positive and negative outcomes for women associated with this distinct type of educational experience. Beneficial outcomes include greater emotional autonomy, increased cross-cultural knowledge, new professional networks, new work skills, and improved English-language competency. Participants within this research report that these benefits have translated into increased respect within their workplaces; new opportunities to represent their organisations at home and abroad; greater participation in international research and policy forums; increased control over negotiations with foreign consultants; and an enhanced commitment to collaboration with other professionals in the ASEAN region. Negative outcomes to arise out of the scholarship experience include role tension and relationship conflict for married women; career disruption associated with employment bonding and job restructuring during the period of absence abroad; new unwanted work responsibilities; and dissatisfaction with some aspects of quality of life in their country of origin. This thesis provides rich narrative material that increases our understanding of the concrete ways that this form of educational aid is ‘lived out’ in the lives and communities of female development scholars.
Keywords: Women; Development; Scholarship schemes; Fields of Research::370000 Studies in Human Society::370100 Sociology::370107 Social change